2015
DOI: 10.3402/qhw.v10.27536
|View full text |Cite
|
Sign up to set email alerts
|

Striking a balance between in-person care and the use of eHealth to support the older rural population with chronic pain

Abstract: New and existing information communication technologies (ICT) are playing an increasingly important role in the delivery of health and social care services. eHealth1 has the potential to supplement in-person home visits for older, rural adults with chronic pain. The Technology to support Older Adults' Personal and Social Interaction project—TOPS—examines interactions between older people and their health/social care providers and considers how eHealth could play a part in enhancing the life experiences of olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 24 publications
0
38
0
1
Order By: Relevance
“…Social behaviours of interest included participants’ duration of speech, with and without eye contact, both when speaking and when spoken to. The social and personal interaction schedule recorded types of interactions that took place, such as ‘humour’ and ‘reassurance touch’, as well as whether these interactions were instigated by home‐care worker or client (Roberts et al, ).…”
Section: Research Aim 1: To Describe the Methodologies That Have Beenmentioning
confidence: 99%
See 4 more Smart Citations
“…Social behaviours of interest included participants’ duration of speech, with and without eye contact, both when speaking and when spoken to. The social and personal interaction schedule recorded types of interactions that took place, such as ‘humour’ and ‘reassurance touch’, as well as whether these interactions were instigated by home‐care worker or client (Roberts et al, ).…”
Section: Research Aim 1: To Describe the Methodologies That Have Beenmentioning
confidence: 99%
“…Ethical considerations: Seven studies reported having obtained ethical approval from an appropriate ethics committee (Casado‐Mejía & Ruiz‐Arias, ; Cataldo et al, ; Kalman & Andersson, ; Roberts et al, ; Sundler et al, ; Swedberg et al, , ). Two studies did not require ethical approval to carry out their observations (Glasdam et al, ; Nielsen & Jørgensen, ), although the authors from one of these studies described following the principles of the Helsinki Declaration which outline the codes of conduct for nursing research (Glasdam et al, ).…”
Section: Research Aim 1: To Describe the Methodologies That Have Beenmentioning
confidence: 99%
See 3 more Smart Citations